Mekanisme Forgiveness Therapy Islami pada Penyelesaian Konflik Setelah Bercerai - Moh. Jeweherul Kalamiah; Abdul Mujib; Ubaidillah Ubaidillah (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
Divorce in Indonesia continues to show an increasing trend each year, leaving unresolved psychological, social, and spiritual impacts even after legal proceedings are finalized. Post-divorce conflicts, such as child custody disputes, property division, and fractured extended family relations, often persist and escalate. This study aims to formulate an Islamic Forgiveness Therapy mechanism as an alternative approach for addressing post-divorce conflicts holistically. This research employs a qualitative approach using a library research method, critically analyzing Western psychological theories, Islamic teachings on forgiveness, and empirical divorce data in Indonesia. The findings indicate that Islamic Forgiveness Therapy can be practically applied through three key components: personal forgiveness, which fosters individual spiritual connection with God; social forgiveness, which restores harmony among extended families; and spiritual reframing, which encourages individuals to perceive conflict as a life test that brings wisdom and spiritual growth. This study confirms that integrating Islamic forgiveness values with modern psychotherapy principles offers a more comprehensive and contextual conflict resolution model. The results imply significant potential for application in educational counseling programs, family court mediation services, and the development of online counseling platforms for Muslim families. Thus, Islamic Forgiveness Therapy is expected to shift the paradigm of post-divorce conflict resolution from mere legal settlement to a sustainable healing process for the heart and soul.